Inovasi Daerah Dalam Pengelolaan Sampah Berbasis Sustainable Development (Studi Pada Tpa Wisata Edukasi Talangagung Kabupaten Malang) - Rodhia Alfadilah (Jurnal Administrasi Publik, 2015)
Abstract: Regional Innovation in Solid Waste Management Based on Sustainable Development (Studies in Educational Tourism of TPA Talangagung Kabupaten Malang). The increasing number of total population has significant impact on the amount of solid waste produced. Â In addition, the types of solid waste become more varied as the consumption is increasing. Solid waste is surely a classical problem that give contribution to pollution and global warming, thus an innovation on solid waste management than can encourage sustainable development is needed. Â Many regions in Indonesian including Kabupaten Malang, when conducting the solid waste management still leaves solid waste that must be disposed of to TPA where waste reaches the final point. Solid waste can be a resource if properly managed, therefore TPA is also need to innovate utilizing the potential of the solid waste. The innovation in solid waste management is important also to change the people mindset about solid waste. The result of the research shows that the innovation is in line with the application of Undang-Undang Nomor 18 Tahun 2008 on solid waste management, the spirit of the management officers namely Dinas Cipta Karya dan Tata Ruang, as well as the potential result of the innovation. Based on the sustainable development principles, the innovation in TPA Talangagung has been giving positive impact in the economic, social, and environment aspects. Keyword: Innovation, Solid Waste, Solid Waste Management, Sustainable Development Abstrak: Inovasi Daerah dalam Pengelolaan Sampah Berbasis Sustainable Development (Studi pada TPA Wisata Edukasi Talangagung Kabupaten Malang). Jumlah penduduk berdampak signifikan pada jumlah sampah yang dihasilkan, jenis sampah juga semakin beragam seiring dengan meningkatnya konsumsi masyarakat. Sampah merupakan masalah klasik yang membawa ancaman pencemaran dan pemicu global warming, sehingga dalam mengelolanya dibutuhkan sebuah inovasi yang mendukung terwujudnya sustainable development. Kebanyakan daerah di Indonesia termasuk Kabupaten Malang dalam mengelola sampah masih menyisakan sampah yang harus dibuang ke TPA, dimana sampah mencapai titik terakhirnya. Sampah dapat menjadi sumberdaya apabila dikelola dengan baik, sehingga TPA juga perlu berinovasi memanfaatkan potensi sampah tersebut. Inovasi dalam pengelolaan sampah penting dilakukan juga untuk mengubah cara pandang masyarakat terhadap sampah. Hasil dari penelitian ini menunjukkan yang mendasari munculnya inovasi di TPA Talangagung adalah Undang-Undang Nomor 18 Tahun 2008 tentang Pengelolaan Sampah, semangat/spirit dari pengelola yaitu Dinas Cipta Karya dan Tata Ruang, serta adanya potensi yang ditimbulkan dari inovasi. Berdasarkan prinsip-prinsip sustainable development, inovasi di TPA Talangagung memberikan dampak positif secara ekonomi, sosial, dan lingkungan. Kata Kunci: Inovasi, Sampah, Pengelolaan Sampah, Sustainable Development